2018
DOI: 10.1177/1533033818782793
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between TNF-α Promoter Gene Polymorphism and Genetic Susceptibility to Cervical Cancer

Abstract: To investigate the association between the susceptibility to cervical cancer and the single nucleotide polymorphisms of 5 tumor necrosis factor-α promoter genes (rs361525, rs1800629, rs1800750, rs1799964, and rs673) in Chinese women. A total of 946 peripheral blood samples were collected from women of Han Ethnicity in Shandong province. Of them, 452 were diagnosed with cervical squamous cell carcinomas. The study also included a control group of 494 healthy women. The targeted single nucleotide polymorphisms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
2
10
0
5
Order By: Relevance
“…A significant link was observed in the case of TNF-α -308 G/A, -238 C/T and -1031 G/A polymorphisms with an increased risk of cervical cancer (LI et al, 2018).…”
Section: Polymorphism For Tnf-α-308 G/amentioning
confidence: 88%
“…A significant link was observed in the case of TNF-α -308 G/A, -238 C/T and -1031 G/A polymorphisms with an increased risk of cervical cancer (LI et al, 2018).…”
Section: Polymorphism For Tnf-α-308 G/amentioning
confidence: 88%
“…showed that the A/A and G/A-A/A genotypes of rs361525 are related to the progression of CIN but not to the eventual occurrence of cervical cancer in Tunisia [41]. In 2018, Li et al reported that the rs361525 A allele is a risk factor for cervical cancer in a Chinese population from Shandong Province, northern China [18], and in 2019, Du et al showed that it is a protective factor against cervical cancer in Sichuan Province, southwestern China [12]. In the current study, the A allele of rs361525 was found to be a risk factor for cervical cancer in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 2001, Jang et al reported that the A allele of rs361525 is a protective factor for cervical cancer in a Korean population [14]. However, in 2018, Li et al reported that the A allele of rs361525 is a risk factor for squamous cell carcinoma in a Chinese population from Shandong Province, northern China [18]. Thus, more populations from different regions should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque, los hallazgos señalan el VPH como un factor de riesgo importante (3), no es causa suficiente para malignidad, ya que gran número de mujeres infectadas con el VPH nunca desarrollaron lesiones cervicales (8). Esto puede sugerir la implicación de los antecedentes genéticos en la transformación maligna de células epiteliales a cáncer de cuello uterino (9). La respuesta inmunitaria a nivel del cuello uterino es compleja, principalmente debido a su participación en los eventos reproductivos.…”
Section: Introductionunclassified
“…Algunos investigadores sugieren que el desarrollo de tumores puede estar relacionado a la predisposición genética del individuo de producir mayores niveles de TNFα. Actualmente, existen estudios enfocados en los efectos de variaciones en la región promotora del gen TNFa y su relación con el cáncer de cuello uterino, encontrándose resultados contradictorios (9,17,(20)(21)(22)(23). Sin embargo, otros autores sugieren que la diferencia entre los niveles de producción de TNFα radica en la base genética de las poblaciones estudiadas (23,24).…”
Section: Introductionunclassified